Analisi dan Simulasi Algoritma TEA (Tiny Encryption Algorithm) untuk Enkripsi dan Dekripsi Pesan Text menggunakan Cryptool2 - Muhammad Femy Mulya; Nofita Rismawati (Teknik Informatika, 2019)
The development of data and information technology and communication at this time is an important part of everyday human life. Along with the times, the human need for information is increasing. as the development of data and information technology that is increasingly advanced and developing, the internet can no longer guarantee to provide data that is safe enough for its users. Data is very important, so the accuracy of the data is needed in the decision making process. The importance of data values causes the availability of data security, so that data falls precisely and accurately on the right party. In this research a data security simulation will be designed using encryption and decryption methods using the TEA (Tiny Encryption Algorithm) algorithm. In the TEA (Tiny Encryption Algorithm) encryption process, this study uses 64 rounds, where each round consists of, addition, key & data substitution, and XOR. The purpose of this study is to analyze, design and implement TEA (Tiny Encryption Algorithm) algorithm in the form of encryption and decryption simulation of text messages (both text and text files), so that text messages (both text and text files) will be safer when sent via email from the sender to the recipient. Thesoftware that will be used to create a simulation of the TEA (Tiny Encryption Algorithm) algorithm uses Cryptool2, which is an Open Source program used to describe the concepts of cryptography and cryptanalysis. The test results prove that this simulation can secure text messages (both text writing or text files) with different character lengths and keys. The longer and larger the size of the text message (either text or text file) and the key, the longer it will take for the encryption process.